On the moral grounds of economic relations: A Maussian approach. (February 2014) - Graeber, David
The gift is not a uniform economic category, since gifts are structured by different economic principles or moral rules which co-exist in all societies. Mauss showed that dominant economic forms, like capitalist markets or the heroic gift, often elevate one principle above the others, but ordinary people must combine them in order to get by. There are three moral grounds for economic relations: communism, exchange and hierarchy. Everyday communism is basic to living in society. It is presumptively eternal, a permanent sense of being mutually indebted. Exchange or reciprocity strives to achieve equivalence, so that indebtedness is temporary and should ideally be cancelled. Hierarchy is a permanent relationship between unequal parties. The rhetoric of reciprocity disguises the working principle, which is precedent. Debt here is irrevocable and transfers pass only one way. Ethnography allows us to conceive of making new societies where the balance of economic principles is different from our own.